Quantitative (177)Lu SPECT (QSPECT) imaging using a commercially available SPECT/CT system - Beauregard, Jean-Mathieu (e-Med, 2011)
Purpose: The combination of single photon emission computed tomography (SPECT) and computer tomography (CT) that incorporates iterative reconstruction algorithms with attenuation and scatter correction should facilitate accurate non-invasive quantitative imaging. Quantitative SPECT (QSPECT) may improve diagnostic ability and could be useful for many applications including dosimetry assessment. Using (177)Lu, we developed a QSPECT method using a commercially available SPECT/CT system. Methods: Serial SPECT of (177)Lu sources (89–12,400 MBq) were acquired with multiple contiguous energy windows along with a co-registered CT, and were reconstructed using an iterative algorithm with attenuation and scatter correction. Camera sensitivity (based on reconstructed SPECT count rate) and dead-time (based on wide-energy spectrum count rate) were resolved by non-linear curve fit. Utilizing these parameters, a SPECT dataset can be converted to a QSPECT dataset allowing quantitation in Becquerels per cubic centimetre or standardized uptake value (SUV). Validation QSPECT/CT studies were performed on a (177)Lu cylindrical phantom (7 studies) and on 5 patients (6 studies) who were administered a therapeutic dose of [(177)Lu]octreotate. Results: The QSPECT sensitivity was 1.08 × 10(−5 )± 0.02 × 10(−5) s(−1 )Bq(−1). The paralyzing dead-time constant was 0.78 ± 0.03 µs. The measured total activity with QSPECT deviated from the calibrated activity by 5.6 ± 1.9% and 2.6 ± 1.8%, respectively, in phantom and patients. Dead-time count loss up to 11.7% was observed in patient studies. Conclusion: QSPECT has high accuracy both in our phantom model and in clinical practice following [(177)Lu]octreotate therapy. This has the potential to yield more accurate dosimetry estimates than planar imaging and facilitate therapeutic response assessment. Validating this method with other radionuclides could open the way for many other research and clinical applications.